TRANSFORMATION OF THE HUMANITARIAN COMPONENT OF HIGHER EDUCATION IN THE CONTEXT OF CONTEMPORARY EDUCATIONAL PROCESSES - Chenbai, Nataliia (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2026)
Introduction. Contemporary higher education develops under the influence of technocratic and market-oriented approaches. This is especially evident in technical universities, where the humanitarian component is often treated as secondary to professional training. At the same time, the information society requires specialists capable of understanding the social, cultural, and ethical consequences of technological development. The aim and tasks. The aim of the article is to identify the peculiarities of the transformation of the humanitarian component of higher education. The tasks are to analyze the main educational traditions, determine the levels of transformation of humanitarian education, and substantiate the need for a balanced educational model. Research methods. The study applies socio-philosophical, historical-philosophical, systemic, and comparative approaches to the analysis of educational transformations. Research results. It is shown that the transformation of the humanitarian component takes place at institutional, content-related, and personal-competence levels. At the institutional level, humanitarian disciplines increasingly depend on professional specialization and labor market demands. At the content-related level, humanitarian education shifts from the transmission of cultural traditions toward the development of information culture, critical thinking, and the ability to analyze the sociocultural consequences of scientific and technological development. At the personal-competence level, it contributes to value reflection, communicative culture, social responsibility, and independent thinking. Discussion. The analysis demonstrates that modern debates on higher education reform concern the correlation between humanistic and utilitarian-pragmatic educational traditions. The key issue is not the rejection of one tradition in favor of another, but their productive combination within a new educational paradigm. Conclusions. Humanitarian education in technical universities should be regarded not as an auxiliary element, but as an essential component of holistic professional training. In the information society, it becomes an important condition for preparing socially responsible specialists capable of understanding the implications of technological development.